2011
DOI: 10.3168/jds.2010-3643
|View full text |Cite
|
Sign up to set email alerts
|

Further investigation of lameness in cows at pasture: An analysis of the lesions found in, and some possible risk factors associated with, lame New Zealand dairy cattle requiring veterinary treatment

Abstract: Previous descriptive analysis of data collected from veterinary visits to lame cows in the Taranaki region of New Zealand between December 1995 and July 2007 showed an association between both breed and age and lesion type and site. However, that simple analysis had significant limitations as it did not take account of more than 2 factors at the same time and did not evaluate the effect of time (either year or season). This analysis was designed to overcome those limitations. First, correspondence analysis, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 28 publications
3
14
0
1
Order By: Relevance
“…Lameness has a major effect on productivity [ 1 ] and compromises welfare in dairy cattle [ 2 ]. Prevention, early detection and treatment of lameness is therefore important to reduce these negative effects of lameness on dairy cows [ 3 , 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lameness has a major effect on productivity [ 1 ] and compromises welfare in dairy cattle [ 2 ]. Prevention, early detection and treatment of lameness is therefore important to reduce these negative effects of lameness on dairy cows [ 3 , 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study found foot lesions in lame dairy cattle associated with housing environment and grazing. Most international studies [ 1 , 3 , 15 , 16 ] were based on whole herd foot trimming records, whereas the present study only included lame cows. Due to time and financial constraints it was not possible to include LS 1 or LS 2 cattle in the study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In pasture-based systems, the non-infectious type claw disorders are by far the most prevalent (Chapter 2). This finding is in agreement with some other research (Lawrence et al, 2011). Approximately 85% of all cows in our dataset had some form of non-infectious claw disorder (a severity score > 0 for an overgrown claw, sole hemorrhage, white line disease, or sole ulcer), while just 2.8% of cows had some form of digital dermatitis (an infectious type claw disorder; Chapter 2).…”
Section: Suboptimal Mobility In Pasture-based Dairy Systems: Causes Asupporting
confidence: 93%
“…El 49% de los callejones se registró con pendiente adecuada, lo que favorece el escurrimiento de agua de lluvia y permite un secado más rápido de los mismos, evitando posibles problemas podales y permitiendo que las ubres lleguen más limpias al ordeño, reduciendo el tiempo empleado en la rutina de ordeño. EL 51% fue descrito como plano o hundido, lo cual puede predisponer a problemas podales y de ubre (Lawrence et al, 2011).…”
Section: Infraestructura En La Finca Lecheraunclassified